Verba Emosi Marah Dalam Bahasa Aceh: Kajian Metabahasa Semantik Alami - Khaira, Cut Nuswatul; Mulyadi, Mulyadi (Mahesa Research Center, 2024)
This article aims to look at the representation of reality in language, especially in the context of using words to express emotions, focusing on the word